‘Hell? Yes!’ Moorean reasons to reject three objections to the possibility of damnation - Rooney, James Dominic (Religious studies, 2026)
Objections to the orthodox doctrine of an eternal hell often rely on arguments that it cannot be a person’s own fault that she ends up in hell. The article summarizes and addresses three significant arguments which aim to show that it could not be any individual’s fault that they end up in hell. I respond to these objections by showing that those who affirm a classical picture of sin have Moorean reasons to reject these objections. That classical perspective holds that all (serious) sin involves choosing eternal destiny apart from God and that no sin could possibly be caused by God. Consequently, it is necessary for ending up in hell that someone commit a serious sin, and it is sufficient for ending up damned that one persists forever in sin. Since the objections conflict with Moorean commitments central to the classical perspective, those who hold to such a classical perspective on sin would have good reason to reject all these arguments, which involve assumptions that would entail that such a perspective is false.